Effect of Al2O3 insertion on the electrical properties of SrTiO3 thin films: A comparison between Al2O3-doped SrTiO3 and SrTiO3/Al2O3/SrTiO3 sandwich structure. (April 2015) - Ahn, Ji-Hoon; Kim, Ja-Yong; Jeong, Seong-Jun; Kwon, Se-Hun
Graphical abstract: Highlights: We systemically investigated the effect of Al2 O3 insertion on the electrical properties of SrTiO3 films in metal–insulator–metal capacitor. Two different ways (Al2 O3 -doped SrTiO3 and SrTiO3 /Al2 O3 /SrTiO3 sandwich structured films) were investigated to find an effective structure for minimizing the leakage current and maximizing the dielectric constant. The leakage current reduction by insertion of an Al2 O3 blocking layer seems to be more applicable than the doping method for an archetypical crystalline high- k dielectric material. Abstract: The effect of Al2 O3 insertion on the electrical properties of SrTiO3 films is systemically investigated in metal–insulator–metal (MIM) capacitor because SrTiO3 films with a high dielectric constant generally suffer from high leakage current problem caused by grain boundaries and a narrow band gap. To find an effective Al2 O3 insertion method, Al2 O3 is inserted into SrTiO3 thin films by two different ways. The first method is doping of Al2 O3 in SrTiO3 thin films and the second method is sandwiching a nanometer-thick Al2 O3 layer between SrTiO3 thin films. With respect to leakage blocking properties, the leakage current of Al2 O3 -doped SrTiO3 films is effectively reduced when the SrTiO3 film becomes amorphous by doping. In case of the SrTiO3 /Al2 O3 /SrTiO3 structure, an Al2 O3 layer with a thickness of more than 1.19 nm effectively acts as a leakage current blocking layer without SrTiO3 amorphization. Moreover, the degradation of the dielectric properties of Al2 O3 -doped SrTiO3 films is more severe, caused by structural degradation, than of SrTiO3 /Al2 O3 /SrTiO3 structured films. Therefore, compared with Al2 O3 -doped SrTiO3, a more than two times higher value (∼45) of the dielectric constant can be obtained in the SrTiO3 /Al2 O3 /SrTiO3 structured films with a similar leakage current density of 10 −7  A/cm 2 .